(untitled) (Global Scientific Review, 2025)
the article examines the role of management activities based on scientific principles in ensuring the effectiveness of educational organizations. Particular attention is paid to the integration of reorganization, coordination and regional approaches that contribute to the achievement of strategic goals and the creation of an adaptive educational environment. The mechanisms for increasing the effectiveness of general education organizations as a system aimed at improving the quality of the educational process are analyzed. The findings emphasize the role of management as a tool for ensuring the sustainable development of educational organizations and their compliance with the requirements of modern society